Proximal humeral fractures in Sweden—a registry-based study. Issue 3 (March 2017) - Sumrein, B.; Huttunen, T.; Launonen, A.; Berg, H.; Felländer-Tsai, L.; Mattila, V.
Abstract Summary Proximal humeral fracture is the third most common osteoporotic fracture. To our knowledge, this is the first nationwide population-based registry study in adults that includes both inpatient and outpatient visits. Thus, we were able to report the true incidence rates and trends in the treatment of proximal humeral fractures. Introduction Proximal humeral fractures are among the most common osteoporotic fractures. Valid epidemiologic population-based data, including both inpatient and outpatient visits, however, are lacking. Methods To investigate the Swedish national incidence rates and treatment trends of proximal humeral fractures, we obtained data from the Swedish Hospital Discharge Register between 2001 and 2012. All adult patients (≥18 years of age) in the Swedish Hospital Discharge Register were included. Outpatient visits have been included in the register since 2001. Results We identified 98, 770 patients (womenn = 72, 063; 73 %) with proximal humeral fractures between 2001 and 2012. In 2001, the sex-specific incidence of proximal humeral fractures was 134.5 per 100, 000 person-years for women and 49.2 for men. In 2012, the corresponding values were 174.6 for women and 68.1 for men, increasing 30 % in women and 39 % in men. A total of 17, 013 surgical procedures were conducted between 2001 and 2012. Open reduction and internal fixation with a plate was the most common procedure (n = 5050, 30 %), followed by endoprosthetic implantation (n = 3962, 23 %) and intramedullary nailing (n = 3376, 20 %). The proportion of surgically treated patients increased from 12.1 % in 2001 to 16.8 % in 2012 for women and from 15.1 % in 2001 to 17.1 % in 2012 for men. Conclusion The Swedish national incidence of proximal humeral fractures has been increasing, although it seems to have peaked in the elderly population during 2008–2010. The rate of surgical treatment has increased substantially, particularly open reduction and internal fixation with a plate. To our knowledge, this is the first nationwide epidemiologic study for Sweden reporting the incidence of proximal humeral fractures and including all inpatient and outpatient visits.